Heating and current drive in STEP: why neutral beam injection is not desirable - Thomas Wilson; Mark Henderson; Hana El-Haroun; Anurag Saigiridhari; Emmi Tholerus (Nuclear Fusion)
Spherical Tokamak for Energy Production (STEP) is the UK’s prototype fusion power plant programme aiming to demonstrate net electrical output from a spherical tokamak. The plasma scenarios require a completely non-inductive current drive for the flat-top and the majority of the ramp-up/down phases. Most of the current ( $\sim {80}% $ ) is self-generated by the plasma pressure gradient with the remainder provided by the heating and current drive (HCD) system. The capabilities and limitations of neutral beam injection (NBI) for current drive in relevant STEP scenarios are presented alongside a discussion of integration challenges. It is demonstrated that, in isolation, NBI has excellent current drive efficiency achieving $ζ = 0.4$ at $ρ = 0$ rising to $ζ = 1.4$ at $ρ = 0.8$ for beam energies $ \unicode{x2A7D} 1{\text{MeV}}$ . NBI current drive in STs also demonstrates a strong up-down asymmetry and weak dependence on the effective charge. However, once considered in an integrated design, the poor wall-plug efficiency, large size and consequent high cost make NBI undesirable in STEP compared to microwave based HCD.